Gaps and bumps in the political history of the internet - Félix Tréguer (Internet Policy Review, 2017)
In the past years, there has been a growing scholarly attention given to "digital rights contention", that is political conflicts related to the expansion or restriction of civil and political rights exerted through, or affected by, digital communications technologies. Yet, when we turn to history to inform contemporary debates and mobilisations, what we often find are single-sided narratives that have achieved iconic status, studies focusing on a handful of over-quoted contentious episodes and generally over-representing North America, or scattered accounts that have so far escaped the notice of internet researchers. How can we explain these gaps in internet histories? How can we go about overcoming them to build a more fine-grained understanding of past socio-legal struggles around human rights in the context of media and communications? This essay calls for advancing the political history of the internet in order to empower scholars, activists and citizens alike as they address current (and future) controversies around internet politics.
Keywords: 300; Internet history; Digital rights; Human rights